Indonesian ELT Students’ Perception Toward British Accent in Speaking Classroom in Tertiary Education - Muhammad Fariz Muzaki; Muhammad Reza Pahlevi; Yuna Tresna Wahyuna (English Language in Focus (ELIF), 2023)
This study looked into how EFL students’ perception British accents in speaking classroom in tertiary education. It sought to understand how the pupils felt about British accents in speaking classroom. A case study strategy and qualitative methodology are being used in this study. In this study, reflective journals were used to collect data. Several themes were highlighted by the research findings. topics pertaining to students' experiences speaking in British accents in classroom. The results indicated that pupils find the British accent is difficult. Students' pronunciation in speaking and grammatical terms is more challenging when they have a British accent. According to the kids, a British accent is an interesting accent for conversing. Moreover, the British accent and speaking mannerism make English pronunciation more official than it is in the United States